2017
DOI: 10.1111/bor.12254
|View full text |Cite
|
Sign up to set email alerts
|

A multiproxy macrofossil record of Eemian palaeoenvironments from Klaksvík, the Faroe Islands

Abstract: Studies of interglacial successions are critical to our understanding of the environmental history of an area. Analyses of macrofossil remains of plants and invertebrates from Eemian sediments exposed in a coastal cliff section at Borðoyarvík near Klaksvík, Bordoy, northeastern Faroe Islands, indicate that the sediments accumulated in a coastal lagoon. The fossil flora comprises tree birch Betula sect. Albae and we suggest that birch forests were found locally at sheltered sites in the area. Tree birch also oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The marine diatoms could thus derive from sea spray during storm events, while the trees could have been transported into the lake from a close-by beach or sand bar during such events. The explanation of both freshwater and marine fossil elements is also discussed by Bennike et al (2017). In general, the data show that the environment was favourable for both terrestrial and aquatic plants.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The marine diatoms could thus derive from sea spray during storm events, while the trees could have been transported into the lake from a close-by beach or sand bar during such events. The explanation of both freshwater and marine fossil elements is also discussed by Bennike et al (2017). In general, the data show that the environment was favourable for both terrestrial and aquatic plants.…”
Section: Discussionmentioning
confidence: 92%
“…Palaeoenvironmental resum e Rasmussen (1972) originally misinterpreted the interglacial clayey organic unit in Klaksv ık as glacially reworked marine coastal sediments from the Klaksv ık fjord because of the presence of marine diatoms, although they were in low abundance. Based on geochemical, micro-and macrofossil analyses, Greve (2001), Wasteg ard et al (2005 and Bennike et al (2017) concluded that the sediments (more or less organic gyttjas) were most likely of lacustrine origin formed in a coastal lake/lagoon. The marine diatoms could thus derive from sea spray during storm events, while the trees could have been transported into the lake from a close-by beach or sand bar during such events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations